Discharge Coefficient for Cylindrical Weirs - Rukaia A. Hussain; Sahar A. Mohammed (Tikrit Journal of Engineering Sciences, 2006)
The hydraulic characteristics of cylindrical weirs under free flow conditions were studied experimentally in order to investigate the discharge coefficient (Cd) and the influence of some significant factors and performance of weirs for discharge measuring. The experimental tests were carried out on three models of weirs in which the diameter of weir (D) was varied three times as: 8.0, 10.0 and 12.0 cm. For each model, a series of measurements were taken to measure coefficients of discharge. Results showed that the coefficient of discharge (Cd) increase with increasing the ratio of head to weir diameter (h/D),and for the same ratio (h/D), the discharge coefficient (Cd) increases with increasing weir diameter.